An Evaluation of the Pre-Service TESL Teacher Education English Studies Syllabus Content - Mohamed Din, Abdul Majid (1994)
This study sought to evaluate the content of the TESL English Studies Syllabus. The syllabus determined the design and content of the TESL English Proficiency Course. The study is aimed at determining practising ESL teachers' and also ESL teacher educators' perceptions as to the usefulness of the skill-areas of the syllabus, the adequacy of the topics listed under the skill-areas and also the adequacy of the suggested learning and teaching activities. Two 82-item questionnaires were administered to a group of 264 ESL teachers and 39 ESL teacher educators who made up the samples of the study. An additional instrument used in this study was the interview sessions. Frequency counts, percentages and means scores were the descriptive statistics used for this study. The mean scores of the two groups of respondents were compared using the t-test of significance. The results showed that generally both groups of respondents perceived the content of the syllabus to be useful and adequate. However, the ESL teachers were undecided as to the adequacy of two of the suggested learning and teaching activities, i.e., debates and writing book reports. As for the ESL teacher educators, they were undecided as to the adequacy of the topics listed under two of the skill-areas, viz., the writing skill-area and the language study-area. The t-tests of significance showed that there were no significant difference in the mean scores of the two groups of respondents pertaining to the question of the usefulness of the listening and language study-areas. But there were significant differences in the mean scores of the two groups of respondents pertaining to the question of the usefulness of the speaking, reading and writing skill-areas. As to the question of the adequacy of the topics listed under the skill-areas, it was found that there were significant differences in the perceptions of the two groups of respondents in the topics listed under all the skill-areas. It was also the same for the suggested learning and teaching activities.